Real Time 3D Echocardiographic Evaluation of Iatrogenic Atrial Septal Defects After Percutaneous Transvenous Mitral Commissurotomy - Devarakonda, Sarath Babu (J Cardiovasc Thorac Res, 2015)
Introduction: Percutaneous transvenous mitral commissurotomy (PTMC) is a safe and effective procedure for relief of severe mitral stenosis. PTMC is being done widely and many transseptal procedures requiring large diameter catheters, sheaths are becoming popular. The knowledge of iatrogenic atrial septal defect (iASD) is vital. This study assessed the use of real-time 3D echocardiography (RT3DE) and incidence of iASD in a cohort of patients undergoing transseptal catheterization during PTMC. Methods: One hundred ten patients underwent PTMC. The reliability and accuracy of RT3DE for iASD detection was determined, RT3DE was compared with 2D echocardiography (2DE) for iASD occurrence, influencing variables analyzed and followed up for 1 year. Results: RT3DE is more reliable and accurate for the study of iASD than 2DE. Color RT3DE detected iASD in 94 (85.5%), with 2DE iASD was detected in 74 (67.3%) (P < .0001).On follow up 85% had iASD post procedure, 56% at 6 months, 19% at 1 year follow up. The mean iASD diameter was 5.41 ± 3.12 mm and area 6.57 ± 3.81 mm(2). iASD correlated with patient height, Wilkins score, pre-PTMC LA ‘v’, and post-PTMC LVEDP. Conclusion: RT3DE imaging is superior in accuracy to traditional 2DE techniques. All the modes of RT3DE are useful in the assessment of iASD. iASD measured by RT3DE correlates with several patient, procedural and echocardiographic variables.